Influence of annealing temperature on the sensitivity of nickel oxide nanosheet films in humidity sensing applications - N. Parimon; M. H. Mamat; A. S. Ismail; I. B. Shameem Banu; M. K. Ahmad; A. B. Suriani; M. Rusop (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Nickel oxide (NiO) nanosheet films were successfully grown onto NiO seed-coated glass substrates at different annealing temperatures for humidity sensing applications. NiO seed layers and NiO nanosheet films were prepared using a sol-gel spin coating and sonicated sol-gel immersion techniques, respectively. The properties of NiO nanosheet films at as-deposited, 300 ℃, and 500 ℃-annealed were examined by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), ultraviolet-visible (UV-vis) spectroscopy, and humidity sensor measurement system. The XRD patterns demonstrate that the grown NiO films have crystalline cubic structures at temperature of 300 ℃ and 500 ℃. The FESEM images show that the large porous nanosheet network spread over the layers as the annealing temperature increased. The UV-vis spectra revealed that all the nanosheet films have the average transmittance below than 50% in the visible region, with absorption edges ~ 350 nm. The optical band gap energy was evaluated in ranges of 3.39 to 3.61 eV. From the obtained humidity sensing results, it shows that 500 ℃-annealed film exhibited the best sensitivity of 257, as well as the slowest response time, and the fastest recovery time compared with others.